Association between urinary cadmium levels and prevalence of coronary artery disease: NHANES cross-sectional study (2009–2018) - Ma, Xuhui; Yang, Yang; Jiang, Qingjun (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveThis study aims to sheds light on the correlation between urinary cadmium (Cd-U) exposure and coronary heart disease (CHD) and the mediating effects of serum alkaline phosphatase (ALP) based on a sample of adults in the United States.MethodsA comprehensive cross-sectional study was performed on 8,998 CHD participants who participated in the National Health and Nutrition Examination Survey (NHANES) from 2009 to 2018. Weighted logistic regression was employed to elucidate the association between Cd-U and the likelihood of CHD. We investigated the link of Cd-U exposure to the prevalence of CHD using limited cubic spline models to analyze the exposure-dose relationship. In addition, mediation analyses were conducted to explore the role of serum ALP in metal exposure-induced CHD.Results8,998 participants were included, and 323 among them were diagnosed with CHD. Our study found that elevated levels of Cd-U in U.S. are linked to a heightened likelihood of CHD. Additionally, there is a non-linear positive correlation between Cd-U and CHD, and a saturation effect was observed. Further mediation analysis revealed that the association between Cd-U and CHD prevalence was mediated through serum ALP mellitus, with the mediation percentage being 2.5% (P value <0.05).ConclusionsOur study indicates a strong association between the levels of Cd-U exposure in urine and the likelihood of CHD, with serum ALP serving as a mediator.